Hierarchical Modeling of Patient and Physician Determinants of Blood Pressure Outcomes in Hypertensive Patients with and without Diabetes: Pooled Analysis of Six Observational Valsartan Studies with 15, 282 Evaluable Patients. (25th September 2017) - Ashy, Noha; Nguyen, Thanh-Nga; Denhaerynck, Kris; Gharaibeh, Mahdi; Alhossan, Abdulaziz; Vancayzeele, Stefaan; Brié, Heidi; Aerts, Ann; MacDonald, Karen; Abraham, Ivo
Abstract : We pooled data from 6 valsartan-related studies including 3, 658 diabetic and 11, 624 nondiabetic patients to evaluate blood pressure (BP) outcomes after approximately 90 days of second- or later-line valsartan treatment. Hierarchical linear and logistic regressions were applied to identify determinants of BP outcomes. Similar reductions in BP values and similar BP control rates were achieved in both groups after approximately 90 days of therapy. The modeling analyses identified several common and different patient- and physician-related determinants of BP outcomes for both groups, many of which are modifiable or clinically manageable. Through varying in terms of association and influence between the diabetic and nondiabetic groups, patient-related determinants included age, BP at diagnosis of hypertension, risk factors, valsartan regimen, concomitant antihypertensive treatment, and adherence; and physician-related determinants included gender, years in practice, and hypertension management. In summary, in both diabetic and nondiabetic patients, the use of valsartan-centric treatment regimens in second- or later-line antihypertensive treatment is associated with significant reductions in BP level and improvement in BP control. The determinants identified in modeling provide guidance to clinicians in the common and differential management of hypertension in diabetic and nondiabetic patients.